Aggregate Outbound Tourism Demand in South Africa: an Econometric Analysis - Ziramba, Emmanuel (Journal of Economics and Behavioral Studies, 2013)
This paper, with the use of annual data covering the period 1975 to 2008, seeks to identify the determinants of outbound tourism demand (outbound tourist outflows) in South Africa. We employ cointegration analysis by utilising an autoregressive distributed lag (ARDL) approach proposed by Pesaran et al. (2001) to make inferences about the long run and short run relationships. The results indicate that in the long run, outbound tourism demand is influenced by the real domestic income and the relative prices. Our results indicate that outbound tourism demand is a luxury good with an income elasticity of 3.5. In the short run, only relative prices have an impact on outbound tourism demand in South Africa. Outbound tourism demand was found to be price inelastic in both periods.